PERAN PROFIL DAN KINERJA GURU DALAM MENINGKATKAN MOTIVASI SISWA BELAJAR AGAMA ISLAM - Samsudin, Samsudin (Fakultas Agama Islam UNDARIS, 2019)
The background of this research is Islamic religious education which is held in the Public High School 1 of Bancak and Senior High School 1 in Tuntang, Semarang Regency, referring to the education profile and professional certificate of a religious teacher, and teacher performance in the teaching and process of learning. Teachers in addition to teach in the classroom must always show their totality in seeking perfection as a figure, so that in themselves students emerge motivation to learn Islam.The method used in this research is field research, namely by conducting direct interviews with teachers, students and principals, and archiving data. This research is aimed at all learning related to Islam, such as the profile of a teacher in the world of education and its role at the time of the community, as well as teacher performance. The profile contents and teacher's performance are expected to become motivators of students learning about PAI.Based on this study ,there are several findings relating to learn of Islamic Education in the State of Senior High School 1 Bancak and Senior High School 1 Tuntang Semarang Regency, such as : 1) the teacher's profile is accordance with the S1 diploma requirements and most of them already to have certificates of expertise as educators. 2) Performance of teachers who are professional in such as making administration of learning, implementation, and filing. 3) The profile and performance of PAI's teacher must to be motivator for their student by learning Islamic religion education and make their students have a good behaviour. Latar belakang yang memunculkan penelitian ini adalah pendidikan agama Islam yang terselanggara di SMK Negeri 1 Bancak dan SMA Negeri 1 Tuntang Kabupaten Semarang mengacu pada profil pendidikan dan sertifikat profesioal seorang guru agama, serta kinerja guru di dalam proses belajar mengajar. Guru selain mengajar di dalam kelas harus selalu memperlihatkan totalitasnya dalam mengupayakan kesempurnaan sebagai figur, agar dalam diri siswa muncul secara sendiri motivasi belajar agama Islam.Metode yang digunakan dalam penelitian ini adalah field research (penelitian lapangan), yaitu dengan melakukan wawancara langsung terhadap guru, siswa dan kepala sekolah, dan pengarsipan data. Penelitian ini ditujukan pada seluruh pembelajaran yang berkaitan dengan agama Islam, seperti profil seorang guru di dalam dunia pendidikan dan peranannya pada saat di lingkungan masyarakat, serta kinerja guru. Muatan profil dan kinerja guru tersebut diharapkan menjadi penumbuh motivasi siswa belajar PAI.Berdasarkan penelitian ini ada beberapa penemuan yang berkaitan dengan pembelajaran PAI di SMK Negeri 1 Bancak dan SMA Negeri 1 Tuntang Kabupaten Semarang, seperti 1) Profil guru sudah sesuai persyaratan ijazah S1 dan sebagian besar sudah mempunyai sertifikat keahlian sebagai seorang pendidik. 2) Kinerja guru yang profesional dalam seperti dalam membuat administrasi pembelajaran, pelaksanaan dan pengarsipan. 3) Profil dan kinerja guru PAI memiliki peranan positif terhadap motivasi siswa dalam mempelajari pendidikan agama Islam dan mengembangkan perilaku yang berkarakter.